2017
DOI: 10.1038/s41598-017-11469-6
|View full text |Cite
|
Sign up to set email alerts
|

Reovirus inhibits interferon production by sequestering IRF3 into viral factories

Abstract: Upon viral infection, an arms-race between the cellular intrinsic innate immune system and viral replication is established. To win this race, viruses have established multiple strategies to inhibit the cellular response. Mammalian reovirus (MRV) constitutes a great model to study pathogenesis and life cycle of dsRNA viruses. It replicates in the cytosol of infected cells by forming viral induced-replication compartments, or viral factories. Little is known about the strategy used by MRV to evade the cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 47 publications
3
35
0
Order By: Relevance
“…Specifically, we propose that incoming cores must establish viral RNA and protein expression, 502 and factory formation around the core, with sufficient speed to prevent detection of foreign virus patterns by the 503 host. Indeed, recent studies showed the ability of reovirus factories to selectively sort IFN signalling components 504 (Stanifer et al, 2017). Our data is therefore consistent with a model where the extent of IFN signalling is inversely 505 related to the efficiency of virus replication; this paradox will be further explored in the discussion.…”
Section: Replication 480supporting
confidence: 84%
See 1 more Smart Citation
“…Specifically, we propose that incoming cores must establish viral RNA and protein expression, 502 and factory formation around the core, with sufficient speed to prevent detection of foreign virus patterns by the 503 host. Indeed, recent studies showed the ability of reovirus factories to selectively sort IFN signalling components 504 (Stanifer et al, 2017). Our data is therefore consistent with a model where the extent of IFN signalling is inversely 505 related to the efficiency of virus replication; this paradox will be further explored in the discussion.…”
Section: Replication 480supporting
confidence: 84%
“…We therefore propose that the polymorphisms likely affect reovirus 840 replication by modulating dsRNA-specific but IFN-independent cellular processes. For example, PKR was 841 previously suggested to promote reovirus replication by terminating host translation outside of viral factories, 842 leaving ribosomes to freely translate reovirus mRNAs at virus factories where host anti-viral factors were 843 excluded (Desmet et al, 2014;Smith et al, 2006;Stanifer et al, 2017;Yue and Shatkin, 1997). We propose a 844 model whereby T3D TD predominantly stimulates RIG-I and IRF3 signalling, with minimal NF-κB activation, 845 leading primarily to expression of IFNs and IFN-dependent genes ( Figure 7E).…”
Section: Discussion 675mentioning
confidence: 99%
“…Two previous studies have suggested that reovirus limits the innate immune response. Reovirus can inhibit IFN production by sequestering IRF3 into viral factories (39). Additionally, reovirus can inhibit IFN signaling by nuclear sequestration of IRF9, which functions with STAT1 and 2 to promote expression of IFN stimulated genes (40).…”
Section: Discussionmentioning
confidence: 99%
“…Type I and Type III IFN are transcriptionally regulated by the transcription factor IRF3 (74, 75). Reovirus can antagonize IFN production by sequestering IRF3 to viral inclusions (76) and infection of gut epithelial cells in vitro and in vivo results in upregulated levels of IFNλ mRNA (7678). It is possible that in MDA-MB-231 cells reovirus is unable to sequester IRF3 to viral inclusions, resulting in robust production of Type III IFN.…”
Section: Discussionmentioning
confidence: 99%